Experiences of foreign students in a Mexican University - Nigra, Sabrina (2024)
The objective of this study was to identify the academic and sociocultural experiences and meanings that foreign students who participated in a mobility program attribute to their stay at the host university. The research was carried out with the purpose of formulating proposals and recommendations to improve the permanence of foreign students and thus progress in the indicators of incoming mobility of the host institution. The approach used was qualitative, with phenomenological design and was carried out in the first semester of the year 2023. The study population consisted of twelve foreign students of the Center for Economic and Administrative Sciences of the University of Guadalajara in Mexico, the data collection technique used was an in-depth interview. The results of the research showed that students in general perceive that the mobility stay allowed them to develop new study and socio-cultural competencies, although they detected several differences in the teaching-learning process with respect to the university of origin that hindered their adaptation process. Regarding the management of the incoming mobility program, foreign students have a positive and enriching perception of their stay, where they broadened their academic and socio-cultural learning, reducing their prejudices and stereotypes. Additionally, they made useful suggestions to improve the dissemination and administrative processes of the internationalization area in order to make the stay of foreign students more pleasant and beneficial.